The Corelation between land use, block size, and the diversity of tree species in Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2024)
It is challenging to provide a meaningful and efficient description of the variety seen in complex multi-species uneven-aged forests. Species variety has traditionally received the most attention, and there are many different ways to measure this diversity. Because trees of varying sizes serve diverse ecological functions, size variety is an essential component of forest biodiversity. Woody plant diversity surveys have a history of ignoring or downplaying size diversity because of its perceived difficulty in handling. Using non-spatial and spatially explicit forestry and diversity features, we examined the size and species diversity of two uneven-aged forests in northern China that were home to multi-species trees. These forests were located in monsoon- and subtropical/warm-temperate climatic zones. We discovered that the patterns of variety in complicated multi-species forests were much better understood when we analysed both species diversity and size diversity. Surprisingly, a saturation curve is seen in the connection between relative abundances dependent on size and individuals. Despite the vast differences in the woodland communities studied, the findings were remarkably consistent across all four plots when non-spatial forestry and biodiversity factors were included.